Behavior of failed bonded interfaces under in vitro cariogenic challenge. Issue 5 (May 2016) - Montagner, Anelise F.; Opdam, Niek J.M.; Ruben, Jan L.; Bronkhorst, Ewald M.; Cenci, Maximiliano S.; Huysmans, Marie-Charlotte D.N.J.M.
Highlights: This is the first study to evaluate the caries susceptibility of failed bonded interfaces. The failed bonded samples showed an intermediate caries development between the non-bonded groups. Lesion development was lowest for the non-bonded samples with bonding applied on the dentin and highest for the non-bonded samples with no bonding on dentin. For the non-bonded groups, the self-etch adhesive showed deeper lesion and more mineral loss than the etch-and-rinse bonding material. Mechanical loading aging resulted in deeper caries lesions than the water storage aging. Abstract: Objective: This in vitro study aimed to compare dentin wall caries development at different composite–dentin interfaces. Methods: Dentin samples (10.4 mm 2 ) were restored with composite resin using two adhesive systems (etch-and-rinse and self-etch techniques). Different composite–dentin interfaces with gaps were produced: (a) failed bonded, which were fractured at interface after being submitted to aging protocols (no aging, mechanical loading or water storage); (b) non-bonded interfaces, both without any adhesive material or with adhesive material applied only on the dentin. Adhesively fractured and non-bonded samples were subjected to a lactic acid gel (pH = 5) caries model with a continuous opening/closing movement of the interfacial gap for 10 days. Transverse wavelength-independent microradiographs were taken, and lesion depth and mineral loss were measured. Data were analyzed with linear mixed-effects regression models. Results: Caries development differed among the composite–dentin interfaces ( p  < 0.001). The non-bonded interface with adhesive material on the dentin showed less lesion depth than the failed bonded groups, while the non-bonded interface without adhesive on dentin showed the deepest wall lesions. Difference between the adhesive systems was observed only in the non-bonded groups ( p  = 0.003), with the self-etch adhesive applied on the dentin showing more severe lesions. Samples broken after mechanical loading aging showed deeper lesions than those broken after water storage ( p  < 0.001). Significance: Composite–dentin interfaces failed after aging presented different demineralization from interfaces that were never bonded, indicating that the restorative treatment changes the tissue in a way relevant to secondary caries development.